Stress and teachers satisfaction with educational work - Kurowicka, Ewelina (Journal of Education, Health and Sport, 2018)
Pedagogical activity is one of the special types of human work. Teachers in their daily work are exposed to various stressful situations. The article characterizes the phenomenon of stress and satisfaction in the teaching profession. The aim of this publication is to show the factors conditioning stress, as well as an indication of ways to deal with it. The article presents stress tests for teachers conducted in Poland and abroad. This article have a review character and has been prepared using international scientific databases such as Elsevier, Springer, Web of Science, and Ebsco.